Ortodoxia pe litere - Platon, Mircea (Editura Christiana, 2006)
Collection of essays published in various magazines
Keywords: Aufsatzsammlung; Romanian literature / Criticism and interpretation; Romanian literature; Criticism; interpretation; etc; Literatur